Bone marrow-derived cells or C-X-C motif chemokine 12 (CXCL12) treatment improve thin endometrium in a mouse model - Yi, Kyong Wook (Biol Reprod, 2019)
Successful implantation and pregnancy is dependent on sufficient endometrial growth during each reproductive cycle. Here, we report the therapeutic effect of either bone marrow-derived cells (BMDCs) or the stem cell chemo-attractant C-X-C motif chemokine 12 (CXCL12) on endometrial receptivity in a murine ethanol induced thin endometrium model. Endometrial epithelial area was significantly increased in mice treated with BMDCs, CXCL12, or by co-treatment with both compared with PBS-treated controls. Ki-67 and CD31 immunoreactivity was significantly higher in mice treated with either BMDCs, CXCL12, or both. The mRNA expression levels of endometrial receptivity markers leukemia inhibitory factor, interleukin-1β, and integrin beta-3 were increased in mice treated with either BMDCs, CXCL12, or both. The mRNA levels of matrix metalloproteinase-2 and -9 were significantly decreased by BMDCs but not by CXCL12. Pregnancy rates and litter size were increased after either treatment. Both BMDCs and CXCL12 displayed a comparable efficacy on endometrial regeneration in mice with thin endometrium. Our findings indicate the potential therapeutic effects of BMDCs and CXCL12 on infertility related to thin endometrium. Bone marrow-derived cells and CXCL12 displayed a comparable efficacy on endometrial regeneration in mice with thin endometrium.